Διαδικασίες κοινωνικού μετασχηματισμού στον Πειραιά : μετακινήσεις, οικογένεια, εργασία. - Benoit-Guilbot, O.; Μαράτου-Αλιμπράντη, Λάουρα; Παπλιάκου, Β.; Σορώκος, Ε.; Τσανίρα, Ε.; Χατζηγιάννη, Ανδρομάχη; Benoit-Guilbot, Odile; Bonoit-Guilbot, O. (ΕΚΚΕ, 1998)
Rèsumè: σ. [305]-307